If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 * 3x + 5y = -17 Multiply 2 * 3 6x + 5y = -17 Solving 6x + 5y = -17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. 6x + 5y + -5y = -17 + -5y Combine like terms: 5y + -5y = 0 6x + 0 = -17 + -5y 6x = -17 + -5y Divide each side by '6'. x = -2.833333333 + -0.8333333333y Simplifying x = -2.833333333 + -0.8333333333y
| 9b+2-(-8b+5)=8b+4 | | 2x^2-9x-8=-3x | | 3x+2x=88 | | 2*3+5y=-17 | | 9x+2-(-8x+5)=8x+4 | | 4(x+1)=2(-x-1) | | 6x^2+4=-5x | | z^2-5z-27=0 | | 4(3n-6)=-3(5-7n) | | 18p+3z-56=14-z | | 9.2x-8=2.2x+13 | | -5+5x= | | 9h^2-16=0 | | -(m-4)=-3(m-6) | | (3x+1)=(2x-8) | | C=(b+rm)(l+t) | | (x-2)*(x+5)=400 | | 5(3m+6)=57 | | -5(x+3)=7-(5+x) | | 12x-4=8x-37 | | 8/5x-3=16-2/5x | | P^2-14p+24=0 | | 3(v-2)-6v= | | 4(4-7n)=2(8-n) | | -6x+-5x= | | (46+2x)(65+2x)=4740 | | 3r^2-24r+45=0 | | 12p^2+8p+1=0 | | 3y^3+16y+5=0 | | 4(-b+7)=-(1+7v) | | (x-8)(x+7)=56 | | 17x+-12=114+3 |